Design and simulation research of riser flexible hang-off system based on variable damping for drilling platform to avoid typhoon. (15th September 2021) - Wang, Zhikun; Zhang, Yanting; Wang, Ruifeng; Chen, Jingkai; Xu, Liangbin; Liu, Jian; Huang, Lumeng
Abstract: Inspired by the technical characteristics of the two modes of hard hang-off and soft hang-off commonly used when hanging risers on drilling platforms to avoid typhoons, a new riser flexible hang-off scheme is proposed to compensate the riser heave dynamic load. The mechanical mechanism of riser flexible hang-off is designed. Two compensation strategies are proposed, including the proportional compensation strategy and the back-pressure variable damping compensation strategy. Aiming at the control method of the compensation strategy of back-pressure variable damping with better compensation effect, the hydraulic system scheme of riser flexible hang-off is designed. In order to verify the feasibility of the hydraulic system, the compensation performance of the riser flexible hang-off scheme subjected to the designed hydraulic system is investigated using Simulink software. The results show that the riser flexible hang-off compensates riser heave dynamic load by 30% under the once-in-a-decade sea conditions in the Western Pacific Ocean. The filling pressure of the gas cylinder and the displacement - voltage gain of the throttle valve are critical to on the system performance. The proposed new riser flexible hang-off system casts light on an alternative compensation for drilling platform to avoid typhoon. Highlights: A new drilling riser hang-off scheme is proposed, which is suitable for drilling platform to avoid typhoon. Through theoretical analysis, the advantages and disadvantages of two control strategies, the proportional compensation strategy and the backpressure variable damping control strategy are obtained. The simulation model of the hydraulic system corresponding to the back pressure variable damping control strategy is established and the compensation effect of the system is verified. The key factors affecting system performance are discussed.